C/C-SiC Composites for Nozzle of Solid Propellant Ramjet - WANG Lingling; JI Alin; GAO Yaqi; CUI Hong; YAN Liansheng; PANG Fei (Journal of Aeronautical Materials, 2017)
Carbon fiber reinforced carbon and silicon carbide matrix composites for nozzle inner of solid propellant ramjet were prepared by using the hybrid process of "chemical vapor infiltration + precursor impregnation pyrolysis (CVI+PIP)". The microstructure, flexural and anti-ablation properties of the C/C-SiC composites and hydraulic test and rocket motor hot firing test for nozzle inner of solid propellant ramjet were comprehensively investigated. The results show that when the flexural strength of the composite reachs 197 MPa, the fracture damage behavior of the composites presents typical toughness mode.Also the composites has excellent anti-ablative property, i.e., linear ablation rate is only 0.0063 mm·s-1 after 200 s ablation. The C/C-SiC component have excellent integral bearing performance with the hydraulic bursting pressure of 6.5 MPa, and the high temperature combination property of the C/C-SiC composite nozzle inner is verified through motor hot firing of solid propellant ramjet.